Etnobotani dan Potensi Aren di Desa Pematang Purba dan Desa Buluh Awar, Sumatera Utara - Andayani Oerta G; Ervizal AM Zuhud; Agus Hikmat (The Ethnobiological Society of Indonesia, 2021)
Aren is a multi purpose plant which has many benefits and economic value for the people in the Pematang Purba village and Buluh Awar village. This study was conducted from February to March 2017 and aims to identify ethnobotany aren aren locally include utilization by the community, potential population of palm and palm conservation development efforts in Pematang Purba village and Buluh Awar village. Retrieving data with in-depth interviews, analysis of vegetation and field observation. The results showed that people in the village of Pematang Purba utilize palm that grows wild as a drink palm wine, roof hut in the fields and the wedding ceremony. While in the village Buluh Awar used as raw material brown sugar, sugar ants and drink palm wine. Assessment of the potential of palm in Pematang Purba village classified as sustainable. Aren conservation efforts in Pematang Purba village by increasing the value-added palm. While in the Buluh Awar village need good cultivation techniques that successful cultivation of high level.